Semantic Functional Grammar and Translation Problems - Labutis, Vitas (Kalbotyra, 2006)
The paper deals with one problem of translation – how and what harmful effect can be made to the target language, (in this case to the Lithuanian language) by poor translations of texts from the second language (i.e. the English language). How scientific researches can be useful?At present the new semantic functional grammar is the most productive of so called Amsterdam school which declares as being the part of theoretical activity of natural language users, explaining and making forms of language models. The background of the two parts “The Theory of Functional Grammar” (Part L, 1989, Part II, 1997) by S. Dik was the theoretical basis for this functional grammar. Its theory was supplemented by A. Siewierska (1991) and the issue “Functional Grammar Studies” and other magazines had developed the ideas for more than twenty years.The most important features of functional grammar: 3) defined layered semantic structure of a sentence, showing the three levels (layers) of semantic predicates and attendant semantic roles, involving semantic predicate and the category of semantics of all possible satellites, 2) invoking speaking activities and their semantic environment and pragmatic functions related to semantics, 3) defining that layered semantic abstracting principles and opportunities to introduce them in particular metalanguage, 4) highlighting the common peculiarities of realization of semantic structures and expressing them in various particular languages.Displacing all these, a successful computer modelling and programming can be expected (it has been already used practically). This situation demands to describe the semantic structure of the sentence of more specific languages according to the same general functional structure, and its functioning consistent patterns and peculiarities in various conditions of creating texts.Layered semantic functional grammar can be a good assistance to simultaneous and written translation as well. Naturally, comprehensive bilingual dictionaries are necessary as well as the semantic typological and comparative grammars of two analogical languages used in translating that define the differences of the languages compared – from typological to functioning in various styles up to pragmatic peculiarities, especially nowadays it is a matter of great relevance to present the comparative grammar handbooks and stylistics (in a broad sense) in the English and Lithuanian languages.